The Impact of Workplace Environment on Expatriates’ Adaptation to New Workplace - Alabi, Boluwatife; Šarkiūnaitė, Ingrida (Vilnius University Open Series, 2022)
As industrialization advances around the world, companies are expanding their operations to other regions of the world, resulting in an increase in demand for expatriates who are required to work outside of their home countries. Expatriates are faced with a lot of changes in the host country (cultural differences, language barrier, etc.) and may also encounter some troubles adapting to the workplace environment (physical environment of the office and the occupational health & safety, relationship with coworkers, working hours, workplace culture, etc.). The workplace environment can affect expatriate adaptation negatively or positively. The research results showed that employees who receive cultural and diversity training from their companies tend to be more productive and are at ease in their new roles. Companies are encouraged to establish a diversified environment for their employees in order to lower the likelihood of early repatriation.